The Political History of Iran: From Monarchy to Islamic Republic - Herman Pelani; Hasaruddin Hasaruddin (Lembaga Sembilan Tiga Community, 2023)
Iran, formerly known as Persia, is one of the oldest countries in the world and has a rich history of approximately 18 dynasties, including the Mede, Sassanian, Samanid, Seljuk, Safavid, Zand, Qajar, and Pahlevi dynasties. The country has undergone significant political changes, transitioning from a monarchy system to an Islamic republic. The Islamic revolution began in 1978 with massive demonstrations against the legitimate government of Reza Pahlevi and was led by Ayatollah Khomeini. Finally, the legitimate government was overthrown, and Iran formally transitioned into the government of the Islamic Republic on April 1, 1979, with the broad Iranian public agreeing to a national referendum. In December of the same year, the country accepted the concept of a theocratic constitution, making Iran an Islamic Republic with the al-Faqih region.